The Effect of Screen Time on Dental Caries in Adolescents: A Narrative Review - Hesty Erika Silitonga; Irfansyah Baharuddin Pakki; Verry Asfirizal; Akhmad Azmiardi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Dental caries is a chronic disease with a high prevalence among adolescents. With the advancement of technology, screen time has become a a daily activity. Excessive screen time can lead to encourage a sedentary lifestyle, which may impact oral health. Objective : This review aims to synthesize scientific evidence from various studies to explain how prolonged screen time contributes to caries risk in adolescents. Research Methods/ Implementation Methods : This narrative review synthesizes relevant research articles to gain a comprehensive understanding of the relationship between screen time and dental caries. Articles were searched through major electronic databases, including PubMed, Google Scholar, and ScienceDirect, focusing on publications from 2016 to 2025. Articles included in the review discussed screen time habits among adolescents, the impact of screen time on dental caries or oral health, were written in Indonesian or English. Results : A literature review of 30 articles reported a positive association between high screen time and increased caries risk in adolescents. Behavioral changes were the main mediators of this association. Many studies described two primary mechanisms: prolonged screen time significantly increased cariogenic dietary habits while using devices and excessive screen time reduces oral hygiene practices. Conclusion/Lesson Learned : Excessive screen time acts as a significant behavioral risk factor for dental caries in adolescents because it can trigger unhealthy dietary patterns and reduce oral hygiene practices. Counseling, reducing screen time, education on tooth brushing, healthy eating, and fluoride using can reduce the risk of dental caries.